Devotion and commandment : the faith of Abraham in the Hasidic imagination - Green, Arthur (The Gustave A. and Mamie W. Efroymson memorial lectures, 2015)
"What was piety like before the commandments were revealed? How did Abraham live in a way that fulfilled the ideals of piety without the Torah? This question, raised in the ancient Jewish theology of Philo and central to the struggle of Paul with his own Judaism and his emerging Christian faith, was raised once again by the Hasidic masters of Eastern Europe in the eighteenth century. In a series of powerful and spiritually searching sermons, the Hasidic masters reinterpret spiritually the ancient rabbis' insistence that the patriarchs lived within the Law. In centering their spiritualization of Judaism around the figure of Abraham, these latter-day Jewish thinkers express a position that stands midway between the claims of the Talmud and those of the Christian apostle. Arthur Green uses this Hasidic debate on the patriarchs and the commandments as a point of departure for a wide-ranging consideration of the relationship between piety and commandment in Hasidic Judaism. The result of this effort is a series of rather remarkable mystical defenses of the commandments and an original contribution of Hasidic thought to the ongoing history of Judaism"--